EUMKPS: the process for publishing one book takes more than 12 month - Mat Ripin, Mohd Hamimi; Mohamad, Mohd Suhairi; Fauzi, Fariz; Fauzi Hasyyati Che Hassan, Fariz; Sayed Abdullah, Sharifah Kamilah (Universiti Teknologi MARA, Kedah, 2019)
e-UMKPS is a platform for managing the editorial workflow required to see monographs, edited volumes and, scholarly editions through internal and external review, editing, cataloguing, production, and publication. The process for publishing one book takes more than 12 months. The e-UMKPS manage reduce the process by 3 months from 12 to 9 month per one book.